Antibody targeting tumor-derived soluble NKG2D ligand sMIC provides dual co-stimulation of CD8 T cells and enables sMIC+ tumors respond to PD1/PD-L1 blockade therapy. Issue 1 (26th August 2019) - Zhang, Jinyu; Larrocha, Pablo Saenz-lopez; Zhang, Bin; Wainwright, Derek; Dhar, Payal; Wu, Jennifer D.
Abstract : Background: Insufficient co-stimulation accounts for a great deal of the suboptimal activation of cytotoxic CD8 T cells (CTLs) and presumably unsatisfactory clinical expectation of PD1/PD-L1 therapy. Tumor-derived soluble NKG2D ligands are associated with poor clinical response to PD1/PD-L1 blockade therapy in cancer patients. One of the mostly occurring tumor-derived soluble NKG2D ligands, the soluble MHC I chain related molecule (sMIC) can impair co-stimulation to CD8 T cells. We investigated whether co-targeting sMIC can provide optimal co-stimulation to CTLs and enhance the therapeutic effect of PD1/PD-L1 blockades. Methods: Single agent therapy of a PD1/PD-L1 blockade antibody or a sMIC-targeting non-blocking antibody or a combination therapy of the two antibodies were implied to well-characterized pre-clinical MIC/sMIC + tumor models that closely resemble the NKG2D-mediated oncoimmune dynamics of MIC + cancer patients. Therapeutic efficacy and associated effector mechanisms were evaluated. Results: We show that antibody co-targeting sMIC enables or enhances the response of sMIC + tumors to PD1/PD-L1 blockade therapy. The therapy response of the combination therapy was associated with enhanced antigen-specific CD8 T cell enrichment and function in tumors. We show that co-targeting sMIC with a nonblocking antibody provides antigen-specific CD8 T cells with NKG2D and CD28 dual co-stimulation, in addition to elimination of inhibitory signals, and thus amplifies antigen-specific CD8 T cell anti-tumor responses. Conclusion: Our findings provide the proof-of-concept rationale and previously undiscovered mechanisms for co-targeting sMIC to enable and enhance the response to PD1/PD-L1 blockade therapy in sMIC + cancer patients.